Development of The Soul With The Character of Pancasila for 5th-Grade Students in SD - Fitrian Prila Wardani; Febri Isnawati (International Journal of Science and Applied Science: Conference Series, 2022)
This research aims to develop a mental development program with Pancasila characters for 5th-grade students in elementary school. This program is designed to help students develop the character and values of Pancasila as a basis for behaving and acting. The research was carried out using the development method which involved three stages, namely the definition, development, and evaluation stages. The research was conducted on fifth-grade students at an elementary school in the Jabodetabek area. The results of this study indicate that the Pancasila character development program can improve students’ ability to recognize and apply Pancasila values in everyday life. Apart from that, this program also helps students to develop positive characteristics such as integrity, responsibility, discipline, and social concern.